The Suggested Reciprocal Relationship between Maximum, Minimum and Optimum Usable Frequency Parameters Over Iraqi Zone - Khalid Abdul-Kareem Hadi; Marwa D. Abdulkareem (مجلة بغداد للعلوم)
In this work, the relationship between the ionospheric parameters (Maximum Usable Frequency (MUF), Lowest Usable Frequency (LUF) and Optimum working Frequency (OWF)) has been studied for the ionosphere layer over the Iraqi zone. The capital Baghdad (44.42oE, 33.32oN) has been selected to represent the transmitter station and many other cities that spread over Iraqi region have represented as receiver stations. The REC533 communication model considered as one of the modern radio broadcasting version of ITU has been used to calculate the LUF parameter, while the MUF and OWF ionospheric parameters have been generated using ASAPS international communication model which represents one of the most advanced  and accurate HF sky wave propagation models. The study has been conducted for the annual and seasonal time periods of the years (2009 and 2014) of the solar cycle 24. The results of the seasonal and annual tests have indicated that the interrelationship between the MUF and OWF with LUF was a fourth order polynomial equation, while the reciprocal relationship between the MUF and OWF was a simple relationship that could be represented by a linear regression equation. The reciprocal relationships between MUF, LUF and OWF parameters (present values) have shown a good fitting with the data generated using the international models (predicted values) and theoretical values calculated from the criterion equation.